How Does The Relationship Between Lifestyle With Consumer Decisions In Buying Motorbikes? - Hapsawati Taan; Djoko Lesmana Radji (Universitas Negeri Gorontalo, 2019)
This study aims to test and analyze the influence of lifestyle on purchasing decisions of Yamaha ZR vega motorcycles at PT. Hasjrat Abadi Gorontalo. This research uses quantitative methods. Respondents are they who ever buy vega zr motors for three last years of 2016, 2017, 2018 that all over 97 people. Data were analyzed using simple regression analysis. The results showed that lifestyle variables had a significant effect on purchasing decisions at PT Hasjrat Abadi Gorontalo City. Suggestions should the leadership of PT Hasjrat Abadi Kota Gorontalo pay more attention to consumer lifestyles, for example, from various motor designs, motorcycle brand images and promotions. In addition, it is expected to pay more attention to the selection of inadequate alternatives and the lack of products with the latest models.